Data on the removal of metals (Cr, Cr, Cd, Cu, Ni, Zn) from aqueous solution by adsorption using magnetite particles from electrochemical synthesis - Manrique, Julio Jorge; Marriaga Cabrales, Nilson; Hernández Ramírez, Aracely; Machuca Martínez, Fiderman (Elsevier, 2019)
Magnetic materials are promising adsorbents for removing heavy metals from polluted wastewaters. Magnetite particles were prepared by electrolytic synthesis (average crystallite size 37.9±1.2nm, surface area ¼ 17.2 m2g1, isoelectric point ¼ 6.3, magnetic saturation ¼ 62 emu g1) and used as adsorbent of heavy metals in aqueous solutions. The adsorption capacity of the magnetite was highly dependent on pH value, for Cdþ2, Znþ2, Niþ2 and Cuþ2 the removal performance was higher that 80% at pH ¼ 8. For Crþ6, the acid pH showed removal percentage higher that 90%. The adsorbent was separated from the system, reactivated and reused in subsequent tests using batch adsorption. It was found that removal efficiencies were higher than 70% even during a third cycle of adsorption. Finally, the kinetic behavior of the adsorption of each adsorbate was described by a first-order. The range of values of qe(mg/g) and k (min-1) were 1.3166e1.6367 and 0.0377 to 0.0826 respectively.